2023
DOI: 10.1002/cac2.12429
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell atlas reveals a distinct immune profile fostered by T cell‐B cell crosstalk in triple negative breast cancer

Abstract: Background: Characterizing the unique immune microenvironment of each tumor is of great importance for better predicting prognosis and guiding cancer immunotherapy. However, the unique features of the immune microenvironment of triple negative breast cancer (TNBC) compared with other subtypes of breast cancer remain elusive. Therefore, we aimed to depict and compare the immune landscape among TNBC, human epidermal growth factor receptor 2-positive (HER2 + ) breast cancer, and luminal-like breast cancer.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…VCAM-1 in endothelial cells stimulates TNBC cells to adhere to endothelial cells and mediates the migration of TNBC cells through the endothelial cell layer (mediated by CTGF) [ 49 ]. Regulatory T cells (Treg) are enriched in TNBC tissues, CD8 + T cells are depleted, and some cytotoxic CD8 + T cells are in a state of transition to failure, indicating that their tumor-toxic activity is inhibited [ 50 ]. These cells may be targeted for the treatment of TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…VCAM-1 in endothelial cells stimulates TNBC cells to adhere to endothelial cells and mediates the migration of TNBC cells through the endothelial cell layer (mediated by CTGF) [ 49 ]. Regulatory T cells (Treg) are enriched in TNBC tissues, CD8 + T cells are depleted, and some cytotoxic CD8 + T cells are in a state of transition to failure, indicating that their tumor-toxic activity is inhibited [ 50 ]. These cells may be targeted for the treatment of TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…We then identified all the significant interactions (ligand-receptor pairs) for a list of T cell exhaustion-related pathways and visualized their average expression among different cell subtypes by ComplexHeatmap (version 2.6.2) 75 R package. For a given pair of ligand and receptor, we used a violin plot to visualize their expression levels across groups 76 .…”
Section: Methodsmentioning
confidence: 99%
“…Of all existing types of DCs, pDCs and moDCs seem to have contradictory roles in cancer immunity. Evidence has demonstrated that pDCs infiltrate different types of tumors and are associated with poor outcomes ( 54 ), due to the expression of inhibitory markers including lymphocyte-activation gene (LAG)-3, PD-1, and CTLA-4 ( 55 57 ), the release of immunosuppressive cytokines (e.g., IL-10, TGF-β, and prostaglandin E2) ( 58 ) as well as the expansion and Treg accumulation ( 59 ). However, it has been suggested that pDCs may have a lytic ability against tumor cells ( 60 , 61 ).…”
Section: Dcs and Cancermentioning
confidence: 99%